Applying styryl quinolinium fluorescent probes for imaging of ribosomal RNA in living cells. (March 2020) - Saady, Abed; Varon, Eli; Jacob, Avi; Shav-Tal, Yaron; Fischer, Bilha
Abstract: The detection of subcellular domains in cells can be obtained by specific fluorescent markers. Here we report the use of styryl quinolinium dyes that selectively stain ribosomal RNA (rRNA) in nucleoli and in the cytoplasm of mammalian cells. Specifically, we synthesized a series of 1-methyl-4-(substituted) styryl-quinolinium derivatives, 12a –l . We developed highly efficient microwave-assisted synthesis which prevents the formation of side-products, leading to the products in yields greater than 90%. Compounds 12c-f and 12i in various solvents exhibited maximum absorbance at 500–660 nm, molar extinction coefficient of 25400–49000 M −1 cm −1, and emitted at 630–715 nm. Dyes 12a –l are highly photochemically stable. Dye 12e specifically stained nucleoli and the cytoplasm and is non-toxic. Various tests showed the markedly higher affinity of the dye for rRNA. We demonstrate that 12e is an attractive staining reagent for visualizing and assessing rRNA in both fixed and living cells. Graphical abstract: (E)-2-(3, 5-Difluoro-4-hydroxystyryl)-1, 4-dimethylpyridinium iodide, 12e, is an attractive staining reagent for visualizing and assessing rRNA in both fixed and living cells. Image 1